'Body techniques' as expressive means in the formation of film language in early Soviet cinema. (3rd May 2020) - Stepanova, Polina M.
ABSTRACT: Visual anthropology has opened up new avenues for the analysis of early Soviet cinema (1918–1930s), and Marcel Mauss's theory of 'body techniques' serves to highlight methods for the professional actor's body work and body techniques in cinema, revealing the performative functions of art and life. The philosophy of the new Soviet body is analysed through examples of the professor and mechanic in Congestion (1918); of the child in Wake Up Lenochka (1934); of the old man in The Baltic Deputy (1936); and of the worker in Counterplan (1932). These images lean on archetypal models of corporeal displays and lay the foundation for the perception of a new God-Man (theanthropos). A key aspect in the manipulation of the collective unconscious is the creation of a screen image by actors and non-actors. There is a collision of the psychological way of creating a role in terms of Stanislavsky's school and techniques of extra-ordinary behaviour, which are often shown in the scores of movement of non-actors, while the subtlety of psychological nuances emerges in professional acting. Artificially created, played roles appear more convincing and more life-like than the authentic life of a human body recorded on film.